2020
DOI: 10.1017/jog.2020.42
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the interrelationships among mass balance, meteorology, discharge and surface velocity on Chhota Shigri Glacier over 2002–2019 using in situ measurements

Abstract: The Himalayan glaciers contribute significantly to regional water resources. However, limited field observations restrict our understanding of glacier dynamics and behaviour. Here, we investigated the long-term in situ mass balance, meteorology, ice velocity and discharge of the Chhota Shigri Glacier. The mean annual glacier-wide mass balance was negative, −0.46 ± 0.40 m w.e. a−1 for the period 2002–2019 corresponding to a cumulative wastage of −7.87 m w.e. Winter mass balance was 1.15 m w.e. a−1 and summer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 51 publications
3
51
0
Order By: Relevance
“…Furthermore, u attains a maximum (5.2 m s −1 ) in June, while minimum in March (1.1 m s −1 ). However, Mandal et al (2020) have reported that the higher u was observed in winter (DJFM), whereas lower in summer season (JJAS) for the period from 1 October 2009 to 28 September 2019 recorded at the AWS located in 4863 m a.s.l. over the Chhota Shigri glacier.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, u attains a maximum (5.2 m s −1 ) in June, while minimum in March (1.1 m s −1 ). However, Mandal et al (2020) have reported that the higher u was observed in winter (DJFM), whereas lower in summer season (JJAS) for the period from 1 October 2009 to 28 September 2019 recorded at the AWS located in 4863 m a.s.l. over the Chhota Shigri glacier.…”
Section: Resultsmentioning
confidence: 97%
“…3) clearly indicates cold and dry climatic prevailed in the region. The records from Tso Moriri, Tso Kar 31 Triloknath 40 reflects a decreased in precipitation intensity in Westerlies and also evidence by other records 7,55,56 .This period corresponds to the fall of Harappa civilization and perhaps was responsible for deurbanization. Here, we interpret that during the time of the demise of Harappa civilization dust activity has increased northwestern India (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…The meteorological data, obtained from Chhota Shigri glacier, the nearest weather station (see Fig. 1) show that about 75-80% precipitation in the study area is contributed by the Westerlies 56 . A total of 27 sediment cores were retrieved using piston corer under GLACINDIA project (2015) 57 and a 235 cm long sediment core was selected for extracting porewater samples (at every 5 cm interval) using a syringe connected with 0.25 μm filter at glacier laboratory of Jawaharlal Nehru University (JNU), New Delhi.…”
Section: Methodsmentioning
confidence: 94%
“…(2014) during the 2000–2009 period and measured during the 2010–2019 period by Mandal et al. (2020). (Difference: 2010–2019 minus 2000–2009).…”
Section: Discussionmentioning
confidence: 99%
“…(2019) looked at Trambau Glacier, on a south‐facing slope in the central Himalaya and found significant correlation between annual mass balance and annual precipitation, but no discernible correlation between annual mass balance and summer mean air temperature, while Mandal et al. (2020) found that interannual variability for the mass balance of Chhota Shigri Glacier, on a south‐facing slope in the western Himalayas, was driven by variations in air temperature during the ablation season (June to September). These studies demonstrate that the climate variables that drive changes to glacier mass balance vary spatially across the Himalayas, possibly reflecting a different glacier response where the background climate is different (Sakai & Fujita, 2017; Zhu, Yao, Yang, Xu, Wu, & Wang, 2018).…”
Section: Introductionmentioning
confidence: 99%